(3TQM CHjGJ eZfi GddHjHs - (3YHO GdbGOQ Hf YeQ GdHZOGOj , J (B1093 (3g` s; (3CHh gTGe GdCfUGQjs ((3CMeO Hf MShfg GdbaUi GdShSi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO abO TQYJ ai TQM CHjGJ eZfi GddHjH dCHh gTGe GdCfUGQi CfTO ai GdNWHI (B: (3hef PG GdPi JQVi SLGjGg cdgG cai GdeQ fHdkG Cf JYO eYGjHg s
(3BNQgG (B:s
(3hHg jVQH GdeKd aiGdhaGA ajbGd Chai ef GdSeDd ai GdjghO HjJ TYQ aEfg TGYQ hCHhg gTGYQ hCNhg TGYQ hcdge eLjO ai GdTYQ hbjd gPg GdbUjOI dTQjM Hf GdSeDd hbjd dZjQg ef PcQ hGddg CYde GfJgi GdLRA GdChd ef TQM ThGgO eZfi GddHjH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdg Jedc HGSe eMeO eMehOs
(3Ke hba Ydi YUHJg SfI (B1321 (3g` s
(3HChdg agQSJ ddeNWhW s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs